Middle School Students' Mathematics Learning Difficulties in Function Material: A Systematic Literature Review - Aqidatul Izzah; Didi Suryadi; Jarnawi Afgani Dahlan; Mirza Aulia (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
This study aims to explore how the difficulties of high school students in learning mathematics, especially in functional materials. The data obtained in this study were 7 out of 22 articles and theses after going through a series of PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) stages with the Systematic Literature Review (SLR) approach. The articles and theses obtained came from Google Schoolar with the help of the Publish or Perish application. Based on the studies that have been analyzed, the results are obtained that students' mathematical difficulties, especially in function, are divided into three major parts, namely difficulties in the learning process, difficulties in working on problems, and internal and external difficulties. On the other hand, there is also an anticipation to reduce the occurrence of mathematical difficulties in students, including creating a supportive learning environment from the way of teaching and educating teachers, student readiness in learning, and comfortable school environments.